PROGRAM PENGEMBANGAN KAWASAN PARIWISATA PANTAI PURUS KOTA PADANG - Riki Ruspianda (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (LPPM), 2019)
Development of tourism object in Padang City contained in RPJMD 2014-2019 Padang City and Strategic Planning from Cultural and Tourism Department of Padang City. Purus Beach is a popular tourism object in Padang City. The existence of Purus Beach hopes can give positive contribution to the society. The objectives from this research are 1) describe the development of Purus Beach by Padang City Government; 2) describe role of the society in supporting development of Purus Beach in Padang. This research used combined method, case study and survey. The result from this research indicated Padang City government stated 3 (three) sectors of development Padang City tourism, those are : revamping integrated tourism destination in Padang City Government; cultural preservation with activating Minangkabau cultural art gallery; traditional games, and doing events based Minangkabau art; and increase partnership and cooperation with other stakeholders. Development program from Purus Beach refers to concept in RIPPDA 2008-2017 Cultural and Tourism Department of Padang City, that is Natural Beach Experience. Involvement or participation from the society in developing Purus Beach is in development planning at Purus subdistrict generally has done in Musrenbag Purus sub district. Then, roles of the society in developing Purus Beach are take care of tourism object, keep cleaning of Purus Beach and create sense of safe and comfort in form of service to the visitors or tourists and uses Purus Beach as a business opportunity. There are three aspects those become focus in society involvement in developing Purus Beach. Those aspects are economics, social and environment